The Value of Mutual Assistance (Ta'awun) in the Qur'an and Its Relevance to the Sakai Sambayan Tradition of the Lampung Community - Syafira, Klara; Ghozali, Abdul Malik; Windari, Fitri; Yanuri, Rohmat (QiST: Journal of Quran and Tafseer Studies, 2025)
This study aims to examine the value of mutual assistance (ta'awun) in the Qur'an and explore its relevance to the Sakai Sambayan tradition of the Lampung community. Employing a qualitative approach through library research, the study draws upon Qur'anic verses, both classical and contemporary exegeses, and anthropological literature on Lampung culture. The findings reveal a significant convergence between the universal Islamic principle of ta'awun and Sakai Sambayan as a form of local wisdom. Both emphasize solidarity, compassion, and communal togetherness, although they differ in origin: ta'awun is derived from divine revelation, while Sakai Sambayan is rooted in cultural tradition. The integration of these values offers substantial implications for strengthening social cohesion, developing character education grounded in spiritual and cultural values, and fostering religious moderation in the face of modern challenges such as globalization and individualism. Therefore, this study highlights that the synergy between Qur'anic teachings and local traditions can serve as strategic socio-religious capital for building a harmonious, caring, and empowered society within the broader framework of Indonesia's socio-religious development.